2019
DOI: 10.3390/app9214672
|View full text |Cite
|
Sign up to set email alerts
|

Porous Thin-Wall Hollow Co3O4 Spheres for Supercapacitors with High Rate Capability

Abstract: In this study, a zeolitic imidazolate framework-67 (ZIF-67) was prepared as a precursor using a facile hydrothermal method. After a calcination reaction in the air, the as-prepared precursor was converted to porous thin-wall hollow Co3O4 with its original frame structure almost preserved. The physical and chemical characterizations of the nanomaterial were analyzed systemically. The electrochemical tests indicate that the obtained Co3O4 possesses large specific capacitances of 988 and 925 F/g at 1 and 20 A/g a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The coupled redox peaks in the CV curves shift positively or negatively with increased scan rates. The classical phenomenon also confirms the pseudocapacitive property of the obtained material [55]. Besides, the relationship of peak currents and the square root of the scan rates delivers a linear response with a steep slope, as described in the inset of Figure 4b.…”
Section: Resultssupporting
confidence: 76%
“…The coupled redox peaks in the CV curves shift positively or negatively with increased scan rates. The classical phenomenon also confirms the pseudocapacitive property of the obtained material [55]. Besides, the relationship of peak currents and the square root of the scan rates delivers a linear response with a steep slope, as described in the inset of Figure 4b.…”
Section: Resultssupporting
confidence: 76%
“…25,26,35,36 This can be attributed that the binary metal ions with multiple oxidation states in BTMOs can exhibit improved Faradaic redox reactions and high electrical conductivity, which is beneficial to obtain high C s and E d . 25,27 Even if the reported BTMOs can deliver high C s compared to the single-component oxides prepared under similar experimental conditions, the C s values of these BTMOs 38,39 In another report, Zhu et al synthesized Mn−Cu-based BTMOs, which showed the C s of only 422 F/g. 36 The C s values of these Mn− Cu-based BTMOs are much lower compared to those of the reported pristine Mn-oxides and Cu oxides.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Numerous strategies have been attempted to enhance the practical C s values of TMOs by increasing the electrical conductivity and redox behavior, comprising the synthesis of BTMOs/mixed metal oxides/ternary metal oxides, controlling the size and morphologies, and the preparation of composites with highly conductive materials. ,, Recently, BTMOs that showed enhanced pseudocapacitive performance than the corresponding single-component oxides, including Ni–Co, Sr–Cu, Mn–Fe, and Mn–Cu oxides, have attracted much attention. ,,, This can be attributed that the binary metal ions with multiple oxidation states in BTMOs can exhibit improved Faradaic redox reactions and high electrical conductivity, which is beneficial to obtain high C s and E d . , Even if the reported BTMOs can deliver high C s compared to the single-component oxides prepared under similar experimental conditions, the C s values of these BTMOs are significantly lower compared to the theoretical C s values of single-component oxides. For example, Yuan et al prepared Ru–Cr-based BTMOs that delivered the C s only 148 F/g, which is very low compared to the theoretical C s of RuO 2 (1400–200 F/g) and Cr 3 O 4 (3560 F/g). , In another report, Zhu et al synthesized Mn–Cu-based BTMOs, which showed the C s of only 422 F/g . The C s values of these Mn–Cu-based BTMOs are much lower compared to those of the reported pristine Mn-oxides and Cu oxides. ,, Since BTMOs exhibited much improved Faradaic redox behavior than TMOs, the low C s values of them might be due to their low conductivities.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cobalt (Co 3 O 4 ) and manganese (MnO 2 ) oxides are particularly popular for supercapacitor applications due to their simple preparation techniques, various morphologies with high surface area, and fast catalytic reactions suitable for fast charge/discharge processes. [7][8][9][10] Although Co 3 O 4 offers good conductivity and electrochemical stability, 11,12 it has poor rate capability and capacity retention. Combining Co 3 O 4 and MnO 2 can synergistically improve supercapacitor performance in all respects, with the hybrid producing more redox reactions than the sum of the individual components.…”
Section: Introductionmentioning
confidence: 99%